DEMAND OF RURAL TOURISM SERVICES. CASE OF TARNAVA MARE AREA, ROMANIA - Arion, Felix; Muresan, Iulia; Cicea, Claudiu (Economics of Agriculture, 2011)
This paper presents the results of a research conducted in Tarnava Mare Area during August 2010 and April 2011. Based on collected data it was established the profle of tourist regarding the main categories of services they are asking for during their stay in this region. Another important aspect in order to adept the supply to tourists needs that was analyzed is represented by the amount the money they are willing to spend on holiday in rural region.